A Pragmatic Analysis on Vague Language Used in Disaster News Articles on Thejakartapost.com - Jaufillaili, Jaufillaili; Nurmalita, Riska; Herawan, Endang (Register Journal, 2021)
This paper presents the findings analysis of categories and functions on vague language used in disaster news articles on Thejakartapost.com based on the theory of Channell (1994). In the journalism context, especially in disaster news article, the information often contains vague language that has imprecise statement since it is harmful. Therefore, to avoid wrong statements, the reporters often use vague language in presenting information accurately. The study employed a qualitative descriptive method. All data were 24 news articles. There were 12 news articles of natural disasters and 12 news articles of human-caused disasters. The period was from April 2018 until March 2019. The findings of this study showed that there were three categories of vague language, namely vague additives to numbers that were realized by approximators and adjectives. The others were vagueness of choice of vague words that were realized by nouns, and vagueness by scalar implicatures that were realized by quantifiers, numbers, and exaggerations. In addition, they also have its functions of vague language. Firstly, giving the right amount of information, it is used since the reporters just shared the right number of information although the exact number was not available. Secondly, filling in lexical gaps of uncertainty, it is used since the reporters wanted to cover the imprecise information with another word, and generalized word that was difficult to identify. Last but not least, self-protection. It is used since the reporters wanted to protect and hedge their statements from imprecise information.Keywords: Vague Language, Categories, News Articles, Disasters, implicature